Citizen Lawsuit in Environmental Cases - Fatah, Abdul (University of Jember, 2019)
The citizen law suit is one of the effective alternatives for the environmental law enforcement. The citizen lawsuit in environmental disputes has been regulated in the PPLH Law specifically Article 91 paragraph (1) and the Chief Justice of the Indonesian Supreme Court Number 36/KMA/SK/II/2013 concerning the Implementation of Guidelines for Handling Environmental Cases. However, there are no specific rules governing citizen lawsuits in Indonesia because it’s not widely known in the Indonesian legal system. This paper argues that there are three main constraints to the practice of citizen lawsuits in environmental cases, namely: (1) the absence of legal rules that specifically regulate citizen lawsuits, especially the reading mechanism; (2) lack of understanding of law enforcement officials (especially judges) regarding citizen lawsuits; and (3) lack of environmental-certified judges in Indonesia, especially in regions. Keywords: Citizen Lawsuit, Environment, Government.